73.4k views
5 votes
3x -1 = 2 (-4) solve the following equation for x​

User Sudha
by
5.0k points

2 Answers

4 votes

Answer:

x= 2.3

Explanation:

3x-1=2 (-4)

3x-1= 2 x -4

(multiply 2 and -4)

3x-1= -8

(subtract one)

3x= -7

(divide by three)

x=2.3

User Jontem
by
5.4k points
3 votes

Answer:

x = - 7/3

Explanation:

3x - 1 = 2(-4)

simplify

3x - 1 = -8

+1 +1

3x = -7

you have to get the variable by itself

x = - 7/3

User Jordan Papaleo
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.